A Qualitative Exploration of Jezebel Stereotype Endorsement and Sexual Behaviors Among Black College Women. (May 2021) - Leath, Seanna; Jerald, Morgan C.; Perkins, Tiani; Jones, Martinque K.
Researchers suggest that the Jezebel stereotype exerts a significant influence on Black women's sexual decision making. The current qualitative study drew upon narrative data from individual, semistructured interviews with 50 Black women (ages 18-24 years) to explore how the Jezebel stereotype influenced their sexual beliefs and behaviors. Using consensual qualitative research methods, the following four themes emerged from the data: (a) how the Jezebel plays a role in their sexual exploration, (b) how the Jezebel contributes to sexual violence against Black women, (c) how the Jezebel is a hypersexual media representation of Black women's sexuality, and (d) how the Jezebel is a negative sexual stereotype within family contexts. Our findings contextualize the enduring role of the Jezebel stereotype as a sexual script for Black women, as we found that many participants chose to adapt their clothing choices or sexual behaviors in light of their awareness and endorsement of the stereotype. The authors discuss the implications of study findings for Black women and girls' sexual socialization and deconstructing deficit-based ideologies of Black women's sexuality.